A reference to the poet’s culture and formation through the book el-omda by ibn rachik - Kerairi, Amar (Journal of Human Sciences, 2021)
This study explores the innate and acquired cultural sources of the poet in old literary criticism. it is based on the work of EL-OMDA for Ibn Rachik El-Kairaouani to determine the conditions of the successful poet according to the referential guidelines of old poetry as an ideal model to be followed.